PENGARUH RETURN ON ASSETS (ROA), DEBT TO TOTAL ASSETS (DTA), CURENT RATIO, FIRM SIZE, SALES GROWTH TERHADAP RETURN SAHAM PADA PERUSAHAAN LQ–45 YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2015-2019 - Achmad Tjahjono; Siti Endarwati; Imam Rudianto (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
Investors must still exercise caution when making investment decisions in order to receive the expected return. Stock returns in Indonesian companies listed on the LQ-45 index between 2015 and 2019 will be examined in this study, which will also look at the impact of total debt on total assets, the current ratio on stock returns, firm size on stock returns, and sales growth on stock returns. This research method is quantitative with the number of research samples as many as 18 companies multiplied byafive-year period (2015-2019), so that 90 financial. reports are obtained. The sampling technique used was purposive sampling. Meanwhile, statistical descriptive analysis, the classical assumption test, multiple linear regression analysis, the F statistical test, the t statistic test, and the coefficient of determination (R2) test are used to analyze the data. The F statistical test yielded a significance value of 0.000less than0.05, indicating that the variables Return on Assets, Debt to Total Assets, Current Ratio, Firm Size, and Sales Growth all affect the stock return variable concurrently. The adjusted R2 value is 84.7 percent, while the remaining 15.3 percent is influenced by other unobserved independent variables.